Implementasi Pembelajaran Kewirausahaan dalam Pembentukan Karakter Mandiri Siswa Kelas XI Madrasah Aliyah Entrepreneur Nurul Qolbi Polorejo Babadan Ponorogo - Oktavia Marfuatul Maslikhah; Ririn Nuraini (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2022)
This study aims to explain entrepreneurial learning, explain the inhibiting and supporting factors for the implementation of entrepreneurship learning in the formation of students' independent character and explain the implementation of entrepreneurship learning in the formation of independent character in class XI Madrasah Aliyah Entrepreneurial Lessons Nurul Qolbi. This study uses data collection techniques through interviews, observation and documentation. The data analysis technique uses an interactive model from Milles and Hubarman in the form of data reduction, data presentation and drawing conclusions. This study resulted in the following conclusions: Based on research on the implementation of entrepreneurship learning in the formation of independent character of class XI students of Madrasah Aliyah